Determining the Cost of Reuse of Disposable Devices in Cardiology - Akçay, A.; Akçay, M. (AVES 105/9 Buyukdere Cad Mecidiyekoy,Sisli, Istanbul 34394, 2019)
Objective: In this study, we aimed to perform a cost minimisa-tion analysis of reuse of single use devices used in the coronary angiography unit after sterilization. Methods: Thirty kinds of disposable devices used in the angiography unit and which were sent to the sterilization unit for reuse were determined. The cost of these materials was based on information provided by purchasing department of the hospital. Payments of staff, amounts and costs of water and electricity used, and expenditures during packaging and sterilization stages were calculated for a single sterilization procedure. Numbers of sterilization procedures projected and amounts of devices purchased were calculated according to the needs between 2014 and 2015 in angiography unit. Accordingly, hospital costs of single use and reuse of the devices was calculated separately. Results: The cost of buying 30 kinds of devices when one piece of each was purchased was 17 839.46 TL. Expenses of preparation stages for reuse was 255.75 TL. When the hospital’s needs for one year was considered, the cost for single use was 4 787 710 TL. On the other hand, when a predicted number of sterilization process was considered, the calculated cost was 2 162 855 TL. The annual total of the expenses in the preparation stage for reuse was calculated as 164 050 TL. The sum of the costs for purchase of new devices and preparation for reuse was 2 162 855 + 164 050 = 2 336 905 TL. The savings of the hospital were calculated as 4 787 710 – 2 336 905 = 2 451 608 TL per year when calculated according to the predicted reuse number. When compared to single use, reuse reduced the costs by 51.2%. Conclusions: It is shown that reuse of disposable materials in coronary angiography unit is an effective method in terms of cost. In particular, reuse of electrophysiology catheters and pacemakers is cost-effective and a medically safe method. Klimik Dergisi 2019; 32(2): 136-45. © 2019, AVES. All rights reserved.
Kardiyolojide Kullanılan Tek Kullanımlık Malzemelerin Tekrar Kullanımı Durumunda Maliyetin Belirlenmesi
Keywords: Coronary Angiography; Cost and Cost Analysis; Equipment Reuse; Single Use